Peran Usaha Mikro Kecil dan Menengah (UMKM) dalam Mendorong Pertumbuhan Ekonomi - Muh. Syata, Wahyu (Indo Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving national economic growth, particularly in creating jobs, reducing poverty, and strengthening income distribution. This research aims to examine the role of MSMEs in economic growth and the challenges faced in the digital era. The method used is a literature review by collecting data from various sources such as books, scientific journals, and official documents. The study results show that MSMEs contribute significantly to the Gross Domestic Product (GDP), support regional development, and improve community welfare. However, MSMEs also face various obstacles such as limited access to financing, low digital literacy, technological limitations, and weak managerial capabilities. Therefore, continuous support from the government, private sector, and society is needed to enhance human resource capacity, expand access to funding, and encourage the adoption of digital technology so that MSMEs can compete in the ever-evolving digital economy ecosystem.